Growing the library’s presence in a university wide student portal - Green, Peter (2005)
The Library and Information Service at Curtin University of Technology had been an early adopter of portal technology, providing the first portal on campus via MyLibrary and in recent years deploying MetaLib as a gateway to scholarly resources, but had also been a strong advocate of a top level, university wide portal. The implementation of a university wide student portal in late 2003 provided the long desired strategic opportunity. Growing the Library's presence in the portal would be a high priority in 2004. While the Library identified a number of opportunities for development the initial focus was reduced to a challenging but manageable few. These would require close collaboration with other university areas and some innovative use of the Library's own system.